2023
DOI: 10.1002/ohn.381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Packing Versus No Packing in Transperforation Myringoplasty for Chronic Tympanic Membrane Perforations

Abstract: ObjectiveTo compare the operation times, graft survival and success rates, audiometric outcomes, and complications of patients who underwent transperforation myringoplasty with and without packing but without perforation rimming.Study DesignA prospective, randomized controlled trial.SettingA university‐affiliated teaching hospital.MethodsWe conducted a randomized controlled trial that enrolled patients who underwent underlay myringoplasty. No patient underwent perforation rimming. Patients underwent myringopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…In fact, there is a paucity of work published on ear packing, except for comparisons of various types of ointment used with the packs. Nevertheless, recent some evidences suggested that the type of EAC packing did not affect the graft outcomes and increase the complications [ 3 , 10 ].This avoids the discomfort of ear pack removal and an unnecessary out-patient visit, thereby potentially reducing the cost of care. Unfortunately, it is relatively common for surgeons to use antibiotic ointment only in EAC packing, this is believed to prevent the infection of graft [ 2 , 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, there is a paucity of work published on ear packing, except for comparisons of various types of ointment used with the packs. Nevertheless, recent some evidences suggested that the type of EAC packing did not affect the graft outcomes and increase the complications [ 3 , 10 ].This avoids the discomfort of ear pack removal and an unnecessary out-patient visit, thereby potentially reducing the cost of care. Unfortunately, it is relatively common for surgeons to use antibiotic ointment only in EAC packing, this is believed to prevent the infection of graft [ 2 , 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent some evidences suggested that the type of EAC packing did not affect the graft outcomes and increase the complications [ 3 , 10 ].This avoids the discomfort of ear pack removal and an unnecessary out-patient visit, thereby potentially reducing the cost of care. Unfortunately, it is relatively common for surgeons to use antibiotic ointment only in EAC packing, this is believed to prevent the infection of graft [ 2 , 3 , 5 ]. However, the fundamental need for preveting graft infection via use of antibiotic ointment has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations